Managing reforestation to sequester carbon, increase biodiversity potential and minimize loss of agricultural land. (February 2016) - Paul, Keryn I.; Cunningham, Shaun C.; England, Jacqueline R.; Roxburgh, Stephen H.; Preece, Noel D.; Lewis, Tom; Brooksbank, Kim; Crawford, Debbie F.; Polglase, Philip J.
Highlights: The multiple benefits of developing (<15 year) tree plantings can be balanced by manipulating planting width and species choice at establishment In highly-cleared areas, such plantings can sequester substantial biomass carbon while improving biodiversity and causing negligible loss to agricultural production. Abstract: Reforestation will have important consequences for the global challenges of mitigating climate change, arresting habitat decline and ensuring food security. We examined field-scale trade-offs between carbon sequestration of tree plantings and biodiversity potential and loss of agricultural land. Extensive surveys of reforestation across temperate and tropical Australia ( N = 1491 plantings) were used to determine how planting width and species mix affect carbon sequestration during early development (< 15 year). Carbon accumulation per area increased significantly with decreasing planting width and with increasing proportion of eucalypts (the predominant over-storey genus). Highest biodiversity potential was achieved through block plantings (width > 40 m) with about 25% of planted individuals being eucalypts. Carbon and biodiversity goals were balanced in mixed-species plantings by establishing narrow belts (width < 20 m) with a high proportion (>75%) of eucalypts, and in monocultures of mallee eucalypt plantings by using the widest belts (ca. 6–20 m). Impacts on agriculture were minimized by planting narrow belts (ca. 4 m) of mallee eucalypt monocultures, which had the highest carbon sequestering efficiency. A plausible scenario where only 5% of highly-cleared areas (<30% native vegetation cover remaining) of temperate Australia are reforested showed substantial mitigation potential. Total carbon sequestration after 15 years was up to 25 Mt CO2 -e year −1 when carbon and biodiversity goals were balanced and 13 Mt CO2 -e year −1 if block plantings of highest biodiversity potential were established. Even when reforestation was restricted to marginal agricultural land (<2000 ha −1 land value, 28% of the land under agriculture in Australia), total mitigation potential after 15 years was 17–26 Mt CO2 -e year −1 using narrow belts of mallee plantings. This work provides guidance on land use to governments and planners. We show that the multiple benefits of young tree plantings can be balanced by manipulating planting width and species choice at establishment. In highly-cleared areas, such plantings can sequester substantial biomass carbon while improving biodiversity and causing negligible loss of agricultural land.